The Determination of the intention to use Islamic banking of Esa Unggul University Students - Sugiyanto; Endah R, Nurjannah; Arief, Muhammad; Abdul Hadi, Dudi (International Journal of Psychosocial Rehabilitation, 2020)
This study empirically examines factors that influence student interest in using sharia banking using a modified Theory of Planned Behavior/TPB approach. By using this model is expected to find a formula that can be used by islamic banking to increase the number of customers among the students. Respondents are Muslim students at the Faculty of Economics and Business at Esa Unggul University which is active in the even semester of 2018. The sample selection using purposive sampling is done by distributing questionnaires to selected classes. From the result of data analysis of attitude variable to behavior, subjective norm, perception control have positive effect to interest of using islamic banking while the level of religiosity, variable of participation in Islamic mass organization and gender does not influence to interest of using Islamic banking but active respondent in Islamic organization and female respondents have higher tendency to use sharia banking.